Effects of early phase 1 cardiac rehabilitation on cardiac function evaluated by impedance cardiography in patients with coronary heart disease and acute heart failure - Wang, Yishu; Xiao, Yanchao; Tang, Jianjun; Liu, Yutao; Li, Hui; Peng, Zengjin; Xu, Danyan; Shen, Li (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To access the impact of phase 1 cardiac rehabilitation (CR) on cardiac function and hemodynamic changes in patients with coronary heart disease (CHD) and acute heart failure (AHF). Method: 98 patients with CHD and AHF were recruited and randomized into two groups. Control group received standard pharmacotherapy and CR group received standard pharmacotherapy combined phase 1 CR. NT-proBNP and hemodynamic parameters measured by impedance cardiography (ICG) were estimated at baseline and at the end of treatment period. Results: Phase 1 CR combined routine medical treatment could lower NT-proBNP levels. Although the post-treatment NT-proBNP level between control group and CR group showed no significant differences, the percentage of high-risk patients was lower in CR group. Similarly, the post-treatment hemodynamic parameters showed no statistically significant differences between control group and CR group. However, most hemodynamic parameters improved in CR group, but not in control group, suggesting that phase 1 CR combined standard pharmacotherapy improved hemodynamic characteristics by elevating cardiac output, ameliorating preload, improving systolic and diastolic function and relieving afterload. Conclusion: Phase 1 CR combined routine medication can improve cardiac function and hemodynamic characteristics in patients with CHD and AHF. Thus, recommendation of phase 1 CR to stable patients is necessary.